(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2022)
The study aimed to identify the degree of occupational immersion of teachers of the schools of the Directorate of Education in the Bani Kenana District from their point of view. The descriptive survey method was used. The study sample consisted of (350) teachers. The questionnaire was used as a tool for the study. The results showed that the degree of immersion practice The job as a whole came with a grade (medium); The results revealed that there were no statistically significant differences in the degree of occupational immersion due to the variable (years of experience، and educational qualification), and there were statistically significant differences in the variable (sex), which came in favor of (males)